KORBAN KEKERASAN DALAM RUMAH TANGGA (KDRT) DAN KONDISI PSIKOLOGIS SISWA DI SMA PGRI PEKANBARU - Suci Priscila; Zulfan Saam; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: One of the most common forms of violence in the community is domestic violence (KDRT). Such actions may occur by parents to their children, husbands, wives or otherwise. but not many know that violence against children can have a negative impact on the lives of children, both physically and psychologically. This study aims to find out the description of the violence received by the students who are victims of domestic violence (KDRT) and to know the psychological condition of the students who are victims of domestic violence (KDRT). Respondents in this study were people who had experienced domestic violence (KDRT), which amounted to 58 respondents. Data were collected using questionnaires. Data were analyzed by using descriptive method. The results showed that violence received by victims of domestic violence (KDRT) is in the low category of 77.58%. Violence received in the form of physical violence, psychological, sexual, and neglect of household. The psychological condition of students who are victims of violence is in the medium category that is equal to 62.06%. The psychological conditions are emotions: anger, pleasure, sadness, and fear. The conclusions of this study are violence received by victims of violence are in the low category with the accepted forms of violence are physical, psychological, sexual, and neglect of the household and the psychological condition of students who are victims of violence are in the medium category, the psychological condition is angry emotion (revenge, angry, hateful), happy, sad (despair, frustrated), and fear (anxiety, anxiety). This research should benefit everyone, especially parents and school.Keyword: Psychological Condition, Victims of Violence